Productivity of Selected Cabbage Varieties under Varying Drip Irrigation Schedules in Humic Nitisols of Embu County, Kenya - Stephen O. Onkoba; Charles N. Onyari; Bernard M. Gichimu (International Journal of Agronomy)
Use of controlled irrigation in vegetable production is considered a viable option for optimizing input use and productivity. This study aimed at assessing the effects of different drip irrigation schedules on productivity and profitability of three cabbage varieties grown in humic nitisols of Embu County. The study was laid out in a split plot design arranged in Randomized Complete Block Design (RCBD). The drip irrigation schedules were allocated the main plots and crop varieties allocated the subplot treatments. Cabbage test varieties investigated were Riana F1 (V1), Gloria F1 (V2), and Triperio F1 (V3). Irrigation schedule one (S1) involved application of irrigation water twice a week, S2 once a week, and S3 once every two weeks. Soil water content was determined before irrigation and then replenished to field capacity using a known volume of water. The data were subjected to Analysis of Variance using SAS version 9.4. Mean separation was done using Fisher’s least significant difference at 95% level of confidence. The findings revealed that the yields and net revenue obtained from different cabbage varieties were not significantly different. However, the cabbage yields and subsequent revenue increased as irrigation frequency increased. The study recommends adoption of irrigation schedule S1 whose productivity remained high despite the high cost of production.